Analysis of Heat Transfer in Shell and Tube Type Condensers - Rifaldo, Zulpikar; Burhan Hafid; Zakir Husin; Etanto Heiliano Wijayanto; Idris, Muhammad (Universitas Medan Area, 2024)
A heat exchanger is a device used to exchange or change the temperature of a fluid by exchanging heat with another fluid. One of the heat exchangers is a surface type condenser where the steam is separated from the cooling water, the steam is outside the pipes while the cooling water is in the pipes at PT. SOCIMAS. At PT. SOCIMAS, the condenser is part of the main cooling system which functions to condense steam into water and maintain the efficiency and work cycle of the turbine high. For this reason, this final project report focuses on condenser analysis. The results obtained from this final project are the value of the inner convection coefficient of 4056.6827 W/(m2.K) and the outer convection coefficient of 97414.18W/(m2.K) . value of heat transfer rate and effectiveness (Îµ) on the condenser PT. SOCIMAS obtained a heat transfer rate of 153.6001264 MW. While the effectiveness (Îµ), obtained 0.99571 % This shows that the condition of the condenser is quite good, because the steam can go to the condenser, so that the rate of heat transfer and the effectiveness of the condenser are able to condense the steam into liquid.